(untitled) (AYUSHDHARA, 2022)
In Ayurveda, it is said that our body as well as diseases are made of foods that we intake. Food has the main impact on our body. Our body is the end product of food that we intake. The wholesome foods build us likewise the unwholesome food impacts that lead to adverse effects in our body. Hence, treatment of the diseases also needs to be planned accordingly. For the same reason, Ahara must have been described as ‘Maha Bhaisajya’ in Kashyap Samhita. Dairy products specially curd, cheese and paneer are becoming part of life as these are easily accessible now. They have become an essential ingredient of junk foods like pizza, burger, pasta etc. People are taking them frequently without any rules and regulations. Some people are compelled to take them due to their busy schedule as they are the packed, ready to eat and easily available food. This type of food impairs Agni (digestive power) of the body, produces Ama and ultimately results into production of Medoroga. Objectives: Since the impact of dairy products on our body is not clearly defined in Ayurveda. So this article attempts to study the role of dairy products mainly curd, cheese & paneer in pathogenesis of Medoroga. Material & Methods: Charak samhita, Sushruta samhita, Kashyap samhita, modern medical textbooks, journals and online data bases were reviewed thoroughly for the study material. The matter was collected and analyzed critically to clear the concept. Results: Curd, cheese and paneer are not recommended to consume regularly because they are heavy to digest and vitiates Vata, Pitta, Kapha and Rakta. Conclusion: The study concludes that regular and unscheduled consumption of dairy products specially curd, cheese and paneer leads to Medoroga.